2014
DOI: 10.3233/wor-141860
|View full text |Cite
|
Sign up to set email alerts
|

"Home is at work and work is at home": Telework and individuals who use augmentative and alternative communication

Abstract: BACKGROUND: Telework, the use of distance communication technologies to participate in the workforce, has been suggested as a promising employment strategy for individuals with disabilities. OBJECTIVE: The goal of this study was to obtain a better understanding of the benefits and negative impacts of telework, as well as the supports and challenges to telework activities, for persons who use augmentative and alternative communication (AAC). METHODS: This study used a series of focus group discussions, conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 0 publications
4
34
0
3
Order By: Relevance
“…McNaughton et al also look at the pros and cons of telework, focusing on people who use augmentative or alternative communication means [40]. They find that the people in their study identified the elimination of travel time and flexible work schedules as a major benefit of telework, while also expressing concerns about feeling isolated and the difficulty of separating their home and work lives.…”
Section: Disability and Working From Homementioning
confidence: 99%
“…McNaughton et al also look at the pros and cons of telework, focusing on people who use augmentative or alternative communication means [40]. They find that the people in their study identified the elimination of travel time and flexible work schedules as a major benefit of telework, while also expressing concerns about feeling isolated and the difficulty of separating their home and work lives.…”
Section: Disability and Working From Homementioning
confidence: 99%
“…Flexible workplaces and work schedules may result in increased job performance, job satisfaction, autonomy, and creativity 33‐35 . The increased utilization of remote work may also yield new employment opportunities for disadvantaged groups, such as those living with disabilities 36 . Other research found jobs consisting primarily of remote work may blur the boundaries between work and personal life, thereby increasing work–family conflict and work‐related stress 37 .…”
Section: Cdc/niosh Future Of Work Initiative Priority Topicsmentioning
confidence: 99%
“…Flexible working arrangements have been associated with improved employee health and well-being, improved management of work and family role conflicts (Mache, Servaty, & Harth, 2020;Rudolph & Baltes, 2017), increased engagement (Anitha, 2014;Conradie & De Klerk, 2019;Rudolph & Baltes, 2017;, greater job autonomy and psychological resources (Mache et al, 2020) and improved commitment. Similarly, remote work has been correlated with outcomes, such as higher productivity, as employees are willing to recommit part of the time saved by not having to commute (McNaughton, Rackensperger, Dorn, & Wilson, 2014), improved morale (Boell, Campbell, Cecez-Kecmanovic, & Cheng, 2013), fewer work interruptions (Gajendran & Harrison, 2007;Kazekami, 2020;McNaughton et al, 2014), better ability to coordinate work and non-work commitments (Boell, Cecez-Kecmanovic, & Campbell, 2016), greater job satisfaction and commitment (Gajendran & Harrison, 2007;Kazekami, 2020), less role stress and work-family conflict (Masuda, Holtschalg, & Nicklin, 2017) and increased work-life balance (Boell et al, 2013).…”
Section: Flexible Working Arrangements Remote Work and Working From Homementioning
confidence: 99%
“…In contrast, the challenges of extensive remote working include reduced teamwork and collaboration (Boell et al, 2013), work-life blurring (Eddleston & Mulki, 2017), increased isolation and lack of meaningful connections with others (McNaughton et al, 2014;Vander Elst et al, 2017), overwork, infringement on family roles and work-family conflict (Eddleston & Mulki, 2017), distractions, loneliness, worry and guilt (Mann & Holdsworth, 2003), increased stress and decreased life satisfaction (Kazekami, 2020).…”
Section: Flexible Working Arrangements Remote Work and Working From Homementioning
confidence: 99%